2013
DOI: 10.5541/ijot.470
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of The Performance of a Small Capacity SI Engine Fuelled with Model Lean Mixture of Biogas

Abstract: In this paper the results of the experimental study on the SI engine using biogas are presented. The experiments were carried out on a petrol engine with a low engine displacement. Typical SI engine was selected in order to evaluate the potential application of gaseous fuel (i.e. biogas). These types of engines are available on a wide scale and commonly used in automotive sector because of the low purchase price and operating costs. It is expected that after minor modifications, the engine can easily operate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The authors report that a lower combustion temperature resulted in a slow release of heat and long duration of combustion in lean conditions. Stoichiometric mixtures had a shorter combustion duration . This corroborates the results of studies in which COV increased with both fuels, natural gas and methane, when λ was higher than 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors report that a lower combustion temperature resulted in a slow release of heat and long duration of combustion in lean conditions. Stoichiometric mixtures had a shorter combustion duration . This corroborates the results of studies in which COV increased with both fuels, natural gas and methane, when λ was higher than 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The emissions were mostly higher in Study 1 (Bio70), although the differences were low, with a maximum of 0.7 g kWh −1 . According to Crookes, this is due to the low calorific value of the CO 2 , which reduces the temperature in the combustion chamber. Yungjin et al reported similar results when using biogas fuels with various CO 2 contents in a micro‐generation spark ignition engine.…”
Section: Resultsmentioning
confidence: 99%